Molecular Characteristics, Synthase, and Food Application of Cereal β-Glucan - Lijing Sun; Mengyun Hu; Jie Zhao; Liangjie Lv; Yelun Zhang; Qian Liu; Li Zhang; Cuihong Yu; Peinan Wang; Qianying Li; Hui Li; Yingjun Zhang (Journal of Food Quality)
Cereal β-glucan is a type of valuable dietary fiber that mainly exists in the aleurone, subaleurone, and endosperm of some cereal grains. β-Glucan is acknowledged as a functional food ingredient owing to its multiple health benefits, including the prevention of diabetes, reduction in the incidence of cardiovascular disease, antitumor effects, antioxidant activities, and immunostimulation. It is well documented that cellulose synthase-like CslF/H/J genes encode synthases responsible for β-glucan biosynthesis in cereal grains. Recently, β-glucan has been widely applied as an emulsion stabilizer, thickening agent, fat substitute, and bioactive ingredient in the food industry due to its water solubility, viscosity, gelation property, and health benefits. Therefore, the present paper aims to review the molecular characteristics, synthase gene family, and food application of cereal β-glucan in recent years.